Popular Religious Preaching as Informal Education and its Impact on Medieval Islamic Culture (American Journal of Islam and Society, 2024)
This study examines popular preaching in medieval Islamic culture, which served as a form of mass education for the public. Public assemblies (majālis) and gatherings were organized by scholars on their initiative of scholars, or by rulers for various purposes. The assemblies took the form of a sermon (khuṭba), preaching (wa‘ẓ), da‘wa, dhikr with a Sufi shaykh, or as a part of a visit (ziyāra) to a shrine of a righteous person. Assemblies and gatherings were held in mosques, in the courts of rulers, or in public places. The goals of these gatherings depended on the desires of their organizers, the time and place in which they were held, and the religious or social events for which they were arranged. Therefore, the nature of gatherings tended toward religious preaching, the personal interest of the organizers, propaganda, political activities, critique and oversight, and sometimes as a form of celebration or leisure. By means ofthese assemblies, some leaders enhanced their status, as well as garnering greater publicity from among the general population. The gatherings displayed the level of knowledge among the educated and among the ‘ulamā’. In addition to the stated objectives of holding these assemblies, this study shows that the primary objective centered on the preserving of Islamic values and moral rules.